2016
DOI: 10.19044/esj.2016.v12n33p281
|View full text |Cite
|
Sign up to set email alerts
|

Insuffisance Rénale Aigue Obstétricale : Expérience De La Maternité Issaka GAZOBY De Niamey (Niger)

Abstract: Introduction Acute renal failure (ARF) is a serious obstetric complication of pregnancy, a real health problem in developing countries. It is more related to the pathologies of pregnancy affecting the mother rather than the fetus. The purpose of our study was to assess sociodemographic, clinical, therapeutic and evolutionary features in obstetric acute renal failure. Materials and Methods: A cross sectional study of 6 months (August 2015- January 2016) was conducted. The study involved pregnant women over 20- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 16 publications
3
5
2
Order By: Relevance
“…The study allowed us to note that most patients were referred from centers peripheral health (76.92%). This finding is identical to that made by Tondi ZMM, et al who reported that 71.9% of the patients in their series had been referred [19]. This high rate references found both in our study and in the international literature shows the inadequacy of the implementation of a decision tree in our maternity hospitals which explains the references of pregnant women at the stage of complications, a situation that could be avoided.…”
Section: Clinical and Paraclinical Datasupporting
confidence: 89%
See 4 more Smart Citations
“…The study allowed us to note that most patients were referred from centers peripheral health (76.92%). This finding is identical to that made by Tondi ZMM, et al who reported that 71.9% of the patients in their series had been referred [19]. This high rate references found both in our study and in the international literature shows the inadequacy of the implementation of a decision tree in our maternity hospitals which explains the references of pregnant women at the stage of complications, a situation that could be avoided.…”
Section: Clinical and Paraclinical Datasupporting
confidence: 89%
“…Oliguria was objectified in 33.33% of patients. Similar rates had been reported by other authors including Tondi ZMM, et al (40.5%) and Ahoui S, et al (44.71%) [19,7]. For Kabbali N, et al more than half of the patients were in oliguria (57%) [29].…”
Section: Clinical and Paraclinical Datasupporting
confidence: 86%
See 3 more Smart Citations